Calendar and monitored insecticide application for the control of cowpea pests - Afun, J.; Jackai, L.E.N.; Hodgson, C. (Elsevier, 1991)
‘Monitored' sprays are applied when the action threshold (AT) has been reached or exceeded, based on monitoring of crop damage or pest infestation, whereas ‘calendar' sprays are applied at specific days after planting without taking into account continued presence or absence of the pest. In this study a comparison was made between monitored and calendar spray applications to determine whether monitored spraying would reduce the number of insecticide applications and still produce yields comparable to calendar spraying. The study focused on four insect pests — the cowpea aphid (Aphis craccivora Koch), legume bud thrips (Megalurothrips sjostedti Tryb.), legume pod borer (Maruca testulalis Geyer) and pod-sucking bugs. These pests damage cowpea at various stages of growth. The trials were carried out at three locations in Nigeria — Ibadan (forest transition zone), Mokwa and Bida (in the southern Guinea savanna zone). At all locations the two calendar schedules used were 7- and 10-day spray intervals. Differences in their effect on insect pest numbers were not significant, neither were there differences in grain yield (p ≥ 0.05). In general, the calendar schedules recorded lower infestation/damage by aphids, flower thrips and pod borers than monitored spraying but grain yields did not differ between them. Monitored spraying required only two sprays at Ibadan and Mokwa and three at Bida. This was half the number used for calendar spraying. Monitored spraying therefore looks quite attractive as a component in the overall management of cowpea pests.